What is intended by the term “participation” and what does it mean to people living with dementia? A conceptual overview and directions for future research - Smith, Sarah Kate; Wolverson, Emma Louise; Mountain, Gail Anne (Frontiers in Rehabilitation Sciences, 2022)
Policy continues to emphasise the importance of wellbeing in dementia. However, there is a vital need for psychosocial interventions that can promote positive outcomes to enhance ‘living well with dementia’. Our developing understanding of what people living with dementia report as being important to them, has resulted in new interpretations of what constitutes wellbeing including constructs such as ‘growth’, ‘purpose’ and ‘participation’. These exciting and important constructs are not currently captured by outcome measures within dementia research. This limits our understanding of the value of psychosocial interventions. This paper explores the concept of participation and how continued participation in social life can make a difference to the rights of people living with dementia as citizens. We will firstly consider why participation is important for how we might measure outcomes in dementia research and care. Secondly, we will explore how we might measure participation. Finally, we will consider the value of participation as a psychosocial outcome in future research.